Building Smart and Good Citizens in The Digital Era Through Citizenship Education in Indonesia - Musa; Baiq Astri Candra Wulan; Abdul Wahab (International Journal of Scientific Research, 2024)
This research seeks to analyze and reflect the urgency of building smart and good citizens in the digital era through the citizenship education program, because it includes efforts to strengthen civic competence in an inclusive and massive manner, citizenship education, and increase youth literacy based on Pancasila and the 1945 Constitution of the Republic of Indonesia. This research was completed based on a qualitative approach, using literature study methods, data analysis techniques, namely reduction, display and verification. The result is, in a world full of easily accessible information, smart citizens must be able to sort and filter correct and trustworthy information. They must have the ability to verify the veracity of information and analyze its sources. This is important to avoid the spread of fake news (hoaxes) and promote accurate knowledge. The digital era also provides many opportunities to participate in people's lives online. Smart citizens can use digital platforms to share ideas, voice opinions, and contribute to issues they care about. They must also be able to communicate well and respect other people's opinions in a digital environment. In addition, Smart citizens must understand the importance of digital ethics in online interactions. They must respect the rights and privacy of others, avoid cyberbullying behavior, and promote a positive and inclusive attitude in cyberspace. Forming good citizens in the digital era means forming individuals who are responsible, empathetic and have social awareness in the use of technology. In order to form smart and good citizens in the digital era, education and awareness of the importance of digital literacy and digital ethics need to be improved. Schools and educational institutions should include subjects that teach technology skills and wise use. Apart from that, the role of parents and the community is also important in providing guidance and good examples in the use of digital technology. In this way, we can create an intelligent, responsible and ethical society in this digital era.